Overestimated Terrestrial Carbon Uptake in the Future Owing to the Lack of Spatial Variations CO2 in an Earth System Model. Issue 4 (19th April 2022) - Peng, Jing; Wang, Yongli; Dan, Li; Feng, Jinming; Yang, Fuqiang; Tang, Xiba; Wu, Qizhong; Tian, Jing
Abstract: Atmospheric carbon dioxide (CO2 ) would be increasing much more if it were not for terrestrial carbon (C) uptake, fueling the drawdown of atmospheric CO2 in vegetation and soil on decadal to centennial time scales. Here, we used a global Earth system model (BNU‐ESM) with two different CO2 data sets (i.e., uniform CO2 vs. non‐uniform CO2 data sets) to simulate the responses of the C balance, particularly to the non‐uniform CO2 effect. Under future conditions of 2071–2100, accounting for spatial variations of CO2 concentrations resulted in 0.51 Pg C yr −1 or 19% additional global net ecosystem production (NEP) inductions relative to the uniform conditions. The reduction in NEP in the future was mostly caused by the reduction in the Northern Hemisphere, within which summer was the season that accounted for the largest fraction of this reduction. Changes in NEP under future conditions differed largely to those under present conditions, resulting from changes in the circulation caused by the non‐uniform CO2 —for example, reductions in evapotranspiration limit water vapor contributions to the lower atmosphere, and substantially diminish convective precipitation, which led to decreased precipitation. Our findings call for more attention to be paid to the influence of spatial variations in CO2 concentration—particularly in the Northern Hemisphere—to better constrain the projected C uptake under future conditions. Also, it highlights the fundamental importance of non‐uniform CO2 in determining the pattern, response, and magnitude of C uptake through to 2100. Plain Language Summary: Atmospheric carbon dioxide (CO2 ) is the largest contributor to the carbon (C) fluxes in terrestrial ecosystems. Here, we used a global Earth system model (BNU‐ESM) with two different CO2 data sets (i.e., uniform CO2 vs. non‐uniform CO2 data sets) to simulate the responses of the C balance, particularly to the non‐uniform CO2 effect. Under the future conditions of 2071–2100, severe reductions in net ecosystem production were shown, compared with that under the present conditions. It highlights the fundamental importance of non‐uniform CO2 in determining the pattern, response, and magnitude of C uptake through to 2100. Key Points: In response to non‐uniform CO2 during 2071–2100, net ecosystem production (NEP) decreased by ∼69% in the Northern Hemisphere Spatial variations of CO2 concentrations lead to a much stronger response of NEP during springtime at high latitudes Evapotranspiration reductions limit convective precipitation and then decrease gross primary production in southern North America, southern East Asia, and central Europe